Recombinant human C1 inhibitor for the prophylaxis of hereditary angioedema attacks: a pilot study. Issue 1 (5th November 2012) - Reshef, A.; Moldovan, D.; Obtulowicz, K.; Leibovich, I.; Mihaly, E.; Visscher, S.; Relan, A.
Abstract Background Hereditary angioedema (HAE) is a disease characterized by recurrent tissue swelling affecting various body locations. Recent literature shows that patients with frequent attacks may benefit from long‐term prophylaxis. This study evaluated the safety and prophylactic effect of weekly administrations of recombinant C1INH (rhC1INH). Methods Patients with a history of HAE attacks occurring ≥every 2 weeks received a once weekly administration of 50 U/kg rhC1INH. Hereditary angioedema attack history was collected at screening. Breakthrough attacks during the study were recorded at each visit. Following a 2‐week run‐in period, HAE patients received 8 weekly rhC1INH administrations and were followed‐up for an additional 6 weeks. Efficacy was evaluated by comparing the HAE attack incidence during the treatment period to the historical attacks over the previous 2 years. Safety evaluation was based on clinical laboratory and adverse events (AEs) reports. Results The 25 participants reported a mean of 0.9 attacks/week over the past 2 years. The mean breakthrough attack rate during the treatment period was 0.4 attacks/week (95% CI 0.28–0.56). A total of 30 treatment‐emergent‐AEs were reported in 13 patients, all mild to moderate. One patient died from a laryngeal attack 25 days after last study drug administration. The only possible drug related AEs reported were dry mouth, dizziness and anxiety in one patient and hypotension in another. There were no allergic AEs and no neutralizing antibodies observed. Conclusions Weekly administrations of 50 U/kg rhC1INH appeared to reduce the frequency of HAE attacks and were generally safe and well tolerated.